Problematika Guru dalam Penggunaan Model Pembelajaran Koperatif Tipe Group Investigation di Kelas VIII SMP Negeri 1 Dompu - Neneng Ayu Wahdania; Ahmad Fauzan; Hariyanto Hariyanto; Muh Zubair (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
This study aims to describe the problems of Civics Teachers in the use of the Group Investigation (GI) Cooperative Learning Model for Class VIII SMPN 1 Dompu. This study uses a qualitative research approach using the phenomenological method. Collecting data in this study using interviews and documentation. The results showed that the Problems of Civics Teachers in the Use of Group Investigation Type Cooperative Learning Model (GI) Class VIII SMPN 1 Dompu, namely: (1) PPKn Teacher Problems (2) Problems of Using Group Investigation Type Cooperative Learning Models in Civics Subjects Class VIII SMPN 1 Dompu and (3) PPKn teacher problems using the Group Investigation type of cooperative learning model in the Civics Class VIII subject at SMPN 1 Dompu.